Dapagliflozin Modulates the Fecal Microbiota in a Type 2 Diabetic Rat Model - Yang, Mei; Shi, Fang-Hong; Liu, Wen; Zhang, Min-Chun; Feng, Ri-Lu; Qian, Cheng; Liu, Wei; Ma, Jing (Frontiers in Endocrinology, 2020)
ABSTRACTS Background: The gut microbiota is recognized as a major modulator of metabolic disorders such as type 2 diabetes. Dapagliflozin, sodium glucose cotransporter 2 inhibitor (SGLT2i), enhances renal glucose excretion to lower blood glucose levels. The aim of the study was to determine the effects of dapagliflozin on gut microbiota type 2 diabetic rat models. Methods: Four-week-old male Sprague Dawley rats (n=24) were fed high-fat diet (HFD) for 8 weeks, and then followed by a single dose of injection of STZ (30mg/kg, ip). They were randomly divided into three groups (n=8). Each group received intragastric infusion of normal saline (2ml, 0.9%) or metformin (215.15mg/kg/day) or dapagliflozin (1mg/kg/day) for 4 weeks. Blood samples were taken during intragastric glucose tolerance. Fecal samples were collected to access microbiomes by 16S ribosomal RNA gene sequencing. Results: Dapagliflozin significantly decreased fasting and postprandial blood glucose levels as metformin in type 2 diabetic rats (P<0.001). Enterotypes were composed of Ruminococcaceae after treatment of dapagliflozin. Notably, Proteobacteria (especially Desulfovibrionaceae) was enriched in dapagliflozin group. Conclusion: Dapagliflozin exerted different effects on the composition of gut microbiota, compared to metformin. Combination of these two drugs might be beneficial to improve the structure of gut microbiota in type 2 diabetes.